A Comparison of Learning Outcomes Using Quizizz as Interactive Game Media on Students with Visual, Auditory, and Kinesthetic Learning Styles. - Taslim, A. Mutmainnah; Hamzah, Muh. Qardawi; Alim, Bahrul (Universitas Sulawesi Barat, 2024)
This research aims to investigate the differences in learning outcomes using Quizizz as interactive game media on students with visual, auditory, and kinesthetic learning styles. This research is a quantitative research with 69 participants. Data collection techniques include questionnaires and tests. The research instruments are learning style questionnaire and learning outcome test. Data analysis techniques is one-way ANOVA, preceded by prerequisite tests for normality and homogeneity. The data are normal with a significance value > significance level (0.2 > 0.05) and the data are homogeneous with a significance value > significance level, (0.281 > 0.05). The results of this research have a significance value < alpha level (0.016 < 0.05), indicating that the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted, there are difference in learning outcomes using Quizizz as interactive game media on students with visual, auditory, and kinesthetic learning styles. The learning outcomes between visual and auditory learning styles have a significance value > alpha level (0.576 > 0.05), there is no significant difference. The learning outcomes between visual and kinesthetic learning styles have a significance value < alpha level (0.013 < 0.05), there is a significant difference. The learning outcomes between auditory and kinesthetic learning styles have a significance value > alpha level (0.445 > 0.05), there is no significant difference.